1991
DOI: 10.1103/physrevlett.67.1019
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal dispersion of edge magnetoplasma excitations in a two-dimensional electron system

Abstract: Edge magnetoplasma excitations in a two-dimensional electron system have been studied in radiofrequency experiments which exhibit a strong nonlocal behavior of the plasmon dispersion. The nonlocality is shown to be caused by the diagonal conductivity GXX, which, via a length IOZCTXX, governs the spatial distribution of the plasma charge oscillations in the direction perpendicular to the plasmon wave vector, i.e., to the edge of the two-dimensional layer.PACS numbers: 7I.45.Gm, 73.20.Dx, 73.20.Mf The collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…For a millimeter-size sample at typical magnetic fields (2RϷ1 mm, Bϭ10 T͒, the ratio ⌫ M Ϫ1 /t rev ϳ1 (25) for M ϭ50 (20). The revival structure of EMP WP disussed in Sec.…”
Section: Nonpolar Semiconductors: Si and Gementioning
confidence: 99%
See 1 more Smart Citation
“…For a millimeter-size sample at typical magnetic fields (2RϷ1 mm, Bϭ10 T͒, the ratio ⌫ M Ϫ1 /t rev ϳ1 (25) for M ϭ50 (20). The revival structure of EMP WP disussed in Sec.…”
Section: Nonpolar Semiconductors: Si and Gementioning
confidence: 99%
“…Experimental studies [17][18][19][20][21][22][23][24]10,14 of EMP's have employed different excitation processes, including capacitive coupling 21 or Ohmic contacts 22 between the QH edge and an exciting voltage pulse. This paper is motivated most strongly by the capacitive coupling 21 approach and we comment later on the interpretation of these experiments.…”
Section: ͑1͒mentioning
confidence: 99%
“…In 6.9. Its value is found to be ~11, most probably enhanced by the presence of the metal surfaces along the sample [13], which distort the electric field lines.…”
mentioning
confidence: 95%
“…However, very few experiments have actually traced a logarithmic dependence, as this would require a variation of the parameter ql over a wide range. At relatively low frequency, Grodnenski et al [13] have found evidence for a logarithmic dependence by varying σ xx , hence l, with temperature. At high frequency, Dahl et al [14] have reported a fixed value for l independent of B, in contrast with Eq.…”
mentioning
confidence: 99%
“…Therefore, for v = 10 4 − 10 5 m/s, the edge modes of such a drum can be 'heard' in the frequency range ≈ 1 − 100 GHz or, in other words, with microwaves. Such modes have already been observed using spectroscopy [3][4][5][6][7][8][9][10][11] in samples on the millimeter scale and analyzed using semiclassical models, 12,13 and have also been observed through time resolved measurements. [14][15][16][17][18] Here, we focus exclusively on the absorption spectrum of micron-scale samples tuned to quantum Hall plateaus.…”
Section: Introductionmentioning
confidence: 88%